5-Chloro-2-hydroxybenzaldehyde 4-ethylthiosemicarbazone - Lo, Kong Mun (International Union of Crystallography, 2011)
In the title compound, C(10)H(12)ClN(3)OS, the –C=N–N–C– chain bridging the ethylimino group and the benzene ring adopts an extended conformation with a C—N—N—C torsion angle of −171.98 (11)°. The imino H atom of the chain is a hydrogen-bond donor to the S atom of an inversion-related molecule, forming a supramolecular dimer. The hydroxy H atom is intramolecularly hydrogen bonded to the azomethine N atom.